Evaluasi Pengelolaan Tempat Penyimpanan Sementara (TPS) Limbah B3 Pada PT X - Naura Nisrine Hidayatullah (Pusat Riset dan Inovasi Nasional, 2024)
PT X is a company engaged in house building materials and in the process of production activities produces B3 waste. The company is located in Tamanharjo Village, Malang Regency, East Java. The purpose of this study is to evaluate the B3 Waste Temporary Storage Site (TPS) owned by PT X. Evaluation activities are carried out by looking at the existing conditions of the TPS and adjusted to the regulations of PP No. 22 of 2021 and PermenLHK No. 6 of 2021. Judging from the existing conditions, the TPS does not have a logo or partition that is in accordance with the applicable regulations. The evaluation results show that the B3 Waste Temporary Storage Site (TPS) owned by PT X is not in accordance with applicable regulations so that re-design activities need to be carried out.